Effect of particle shape and roughness on the hydrophobicity of low-rank coal surface. Issue 12 (1st December 2020) - Wang, Shiwei; Fan, Huidong; He, Huan; Tang, Longfei; Tao, Xiuxiang
ABSTRACT: In this paper, a relationship between the roundness, roughness and induction time of low-rank coal particles was investigated. With the increase of grind time from 1 to 5 minutes, the roundness of low-rank coal particles slightly increased. The results of induction time measurements indicated that the particle surface roughness played a significant role in the surface hydrophobicity of low-rank coal particles. Moreover, it was also found that the roundness and roughness of low-rank coal particle surfaces presented a certain degree of change after both grinding and abrasion processes. Contrary to roundness change, during the grinding process, the roughness of low-rank coal particles significantly decreased. It was also observed that the roundnesses of low-rank coal samples after the grinding process significantly increased with the increase of abrading time. However, unlike the roundness increase with the abrading time increase, the roughness of low-rank coal samples significantly decreased. Therefore, the induction times of low-rank coal samples showed an increased trend after the grinding and abrading processes, which may be attributed to the difficult rupture of wetting film on the smooth solid surface. The grinding and abrading processes may result in a further decrease in surface hydrophobicity and adversely impact on the flotation performance of low-rank coal.